Generation of 3D models of victims within their surroundings at rescue sites - Kriebisch Susann; Bruder Ralf; Ernst Floris (Current Directions in Biomedical Engineering, 2023)
The use of state-of-the-art technology in emergencies enables fast assessment of the situation. Modern rescue robots, but also rescuers with camera systems, record vast amounts of image data. In addition to the benefits for rescue operations, a quick overview based on this data can help medical staff in the search for suitable treatment strategies. However, such data must be examined and fused into an intuitive display. In this work, exemplary image streams of RGB-D cameras are searched for victims and transferred into separate 3D models per detected person for subsequent intuitive viewing, rotating, and zooming. The method was tested and preliminary evaluated for its functionality, detail accuracy and readability of textures at the German Rescue Robotics Center.